(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The rise in popularity of the communicative approach in language teaching since the late 1970s primarily focusing on language for meaningful interaction and for accomplishing tasks rather than on learning rules has intensified debate among teachers and researchers on corrective feedback or error correction in second language learning. The concept of corrective feedback has been under analysis for long especially since Hendrickson’s study in 1978 in which he questioned if errors should be corrected and if so which ones, when and how the errors should be corrected.Since communication is a two way process, the teacher and the pupil should make the process of communication effective hand in hand. The former serves as a source of information and transmit the same in the form of message. The later, receives information, responds and serves as a feedback to the process. Hence, the class room activities provide an interesting way of learning any language. It develops self confidence. Successful manipulation of games in class room goes a long way in improving the communication skills of students.The present paper is an attempt to study the instructional strategies adopted by English teachers and classroom participation in English. Teacher Talking Time (TTT) was much more than Student Talking Time (STT). Teachers failed to attend to individual needs of the learners and unaware of language games and role-play. Nor were the classrooms feasible for conducting language games and role play activities. In order to improve the situation teachers need to be trained on the latest trends and discoveries in the field through regular workshops. Teachers and administrators’ traditional mindset of treating English as a subject and not as skill need to be changed. Physical condition of the classroom also needs to be improved.